The pathogenicity and regulation of CD161⁺Th17 lineage cells in rheumatoid arthritis - Basdeo, Sharee Ann (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2015)
Pathogenic Th17 cells, which produce their signature cytokine IL-17, play a key role in autoimmune diseases such as rheumatoid arthritis (RA) and therefore, have been the target of recently developed therapeutics. On the other hand, Treg cells act to constrain effector T cell responses and play an important role in maintaining tolerance. The aim of this study was to investigate the regulation of Th17 cells by Treg cells in the context of the RA joint. In recent years it has emerged that both Treg and Th17 cells exhibit significant functional plasticity, particularly under conditions of inflammation.
Keywords: Immunology, Ph.D.; Ph.D. Trinity College Dublin